Osteomyelitis Due to Multiple Carbapenemase-Producing Gram-Negative Bacteria: The First Case Report of a GES-13-Producing Pseudomonas aeruginosa Isolate in Canada - Shadi Sepehri; Guillaume Poliquin; Nora Alfattoh; David Boyd; Michael Mulvey; Andrew Denisuik; Sergio Fanella; James Karlowsky; Andrew Walkty (Canadian Journal of Infectious Diseases and Medical Microbiology)
A case of osteomyelitis in an infant following a burn injury sustained in Pakistan caused by a GES-13-producing Pseudomonas aeruginosa (the first reported in Canada) and an OXA-48 producing Klebsiella pneumoniae is described. The present case serves to highlight the importance of international travel as a risk factor for infection with carbapenemase-producing bacteria and the challenges in the laboratory detection of these organisms.